Dairy consumption and household diet quality in East Africa: Evidence from survey-based simulation models - Ecker, Olivier; Pauw, Karl (Elsevier, 2024)
Dairy foods are an important source of essential macro- and micronutrients in household diets, and their consumption is associated with reduced malnutrition, especially among young children. Low dairy consumption in many developing countries is a justification for programs that promote dairy livestock ownership, help develop dairy value chains, or stimulate dairy demand. While several studies confirm the beneficial effects of such dairy-specific interventions on nutritional outcomes, the purpose in this study is to consider more broadly the contribution of dairy to overall diet quality. Our assessment of consumer preferences for dairy, coupled with simulations of consumption responses to dairy price and household income changes, provide quantitative evidence that can inform policymakers about the possible effects of public policies on dairy consumption and diet quality. While our analysis is based on data from Kenya and Uganda, both countries with established dairy sectors, our findings are relevant for other East African countries with similar dietary patterns and emergent dairy sectors.